Effect of Cathodal Transcranial Direct Current Stimulation for Lower Limb Subacute Stroke Rehabilitation - Qian Duan; Wenying Liu; Jinhui Yang; Ben Huang; Jie Shen (Neural Plasticity)
Background and Purpose. Motor dysfunction of the lower limb is a common sequela in stroke patients. The aim was to evaluate the efficacy of cathodal transcranial direct current stimulation (ctDCS) combined with conventional gait rehabilitation (CGR) to compare and clarify the clinical rehabilitation efficacy of ctDCS on motor dysfunction of the lower limbs after stroke to improve the walking ability of stroke patients. Methods. A pilot double-blind and randomized clinical trial. Ninety-one subjects with subacute stroke were treated with cathodal/sham stimulation tDCS based on CGR (physiotherapy 40 min/d and occupational therapy 20 min/d) once daily for 20 consecutive working days. Computer-based stratified randomization (1 : 1) was employed by considering age and sex, with concealed assignments in opaque envelopes to ensure no allocation errors after disclosure at the study’s end. Patients were evaluated at T0 before treatment, T1 immediately after the posttreatment assessment, and T2 assessment one month after the end of the treatment. The primary outcome index was assessed: lower limb Fugl-Meyer motor score (FMA-LE); secondary endpoints were other gait assessment and relevant stroke scale assessment. Results. Patients in the trial group performed significantly better than the control group in all primary outcome indicators assessed posttreatment T1 and at follow-up T2: FMA-LE outcome indicators between the two groups in T1 (P=0.032; effect size 1.00, 95% CI: 0.00 to 2.00) and FMA-LE outcome indicators between the two groups in T2 (P=0.010; effect size 2.00, 95% CI: 1.00 to 3.00). Conclusion. In the current pilot study, ctDCS plus CGR was an effective treatment modality to improve lower limb motor function with subacute stroke. The effectiveness of cathodal tDCS in poststroke lower limb motor dysfunction is inconclusive. Therefore, a large randomized controlled trial is needed to verify its effectiveness.